Optimal combination of energy crops under different policy scenarios; The case of Northern Greece. (September 2016) - Zafeiriou, Eleni; Petridis, Konstantinos; Karelakis, Christos; Arabatzis, Garyfallos
Abstract: Energy crops production is considered as environmentally benign and socially acceptable, offering ecological benefits over fossil fuels through their contribution to the reduction of greenhouse gases and acidifying emissions. Energy crops are subjected to persistent policy support by the EU, despite their limited or even marginally negative impact on the greenhouse effect. The present study endeavors to optimize the agricultural income generated by energy crops in a remote and disadvantageous region, with the assistance of linear programming. The optimization concerns the income created from soybean, sunflower (proxy for energy crop), and corn. Different policy scenarios imposed restrictions on the value of the subsidies as a proxy for EU policy tools, the value of inputs (costs of capital and labor) and different irrigation conditions. The results indicate that the area and the imports per energy crop remain unchanged, independently of the policy scenario enacted. Furthermore, corn cultivation contributes the most to iFncome maximization, whereas the implemented CAP policy plays an incremental role in uptaking an energy crop. A key implication is that alternative forms of motivation should be provided to the farmers beyond the financial ones in order the extensive use of energy crops to be achieved. Highlights: A stochastic and a deterministic LP model is formulated. The role of CAP is vital in generated income. Imports and cultivated areas are subsidy neutral. The regime of free market results in lower income acquired from the potential crop mix. Non – financial motivation is a key determinant of the farmers' attitude towards energy crops.